2021
DOI: 10.3390/cancers13081762
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Signature Analysis Implicates Hereditary Cancer Genes in Endometrial Cancer Development

Abstract: Risk of endometrial cancer (EC) is increased ~2-fold for women with a family history of cancer, partly due to inherited pathogenic variants in mismatch repair (MMR) genes. We explored the role of additional genes as explanation for familial EC presentation by investigating germline and EC tumor sequence data from The Cancer Genome Atlas (n = 539; 308 European ancestry), and germline data from 33 suspected familial European ancestry EC patients demonstrating immunohistochemistry-detected tumor MMR proficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…genes in other tumor types with much smaller series (Kondrashova et al, 2021;Stadler et al, 2021) and although several pedigrees with multiple tumor phenotypes have been reported, the data is insufficient to draw conclusions about a broader phenotypic spectrum of the disease. These findings warrant further investigation of non-OC/BC cancer phenotypes with big series and proper case-control studies to better clarify the phenotypic spectrum of the disease.…”
Section: Clinical Relevance and Future Perspectivesmentioning
confidence: 99%
“…genes in other tumor types with much smaller series (Kondrashova et al, 2021;Stadler et al, 2021) and although several pedigrees with multiple tumor phenotypes have been reported, the data is insufficient to draw conclusions about a broader phenotypic spectrum of the disease. These findings warrant further investigation of non-OC/BC cancer phenotypes with big series and proper case-control studies to better clarify the phenotypic spectrum of the disease.…”
Section: Clinical Relevance and Future Perspectivesmentioning
confidence: 99%
“…Our findings add to the debate about a role for BRCA1 in EC risk and propose PALB2 as a gene of interest for further study in this regard. Furthermore, germline and tumor signature analysis of EC sequence data from The Cancer Genome Atlas has provided support that germline loss‐of‐function variants in homologous recombination genes, including BRCA1 and PALB2 , can sometimes contribute to endometrial tumor development (Kondrashova et al, 2021). That is, irrespective of firm proof of the role of these genes in EC risk, identification of a BRCA1 or PALB2 variant in an individual with EC may have implications for use of targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Mutational signatures from single nucleotide mutations were first described in breast cancer 70 and later characterised across many tumour types 16,17 and now include signatures from small insertions and deletions and chromosome structural variants. 17 These signatures can inform not only on how tumours develop, treatment selection and germline variant classification, [71][72][73] they may also guide long-term clinical management like follow-up frequency and therapeutic manipulation of recurrences and metastasis to improve PFS and OS in a variety of cancers. 63 Tumour burden and disease monitoring Early identification of tumour recurrence and effective tumour burden monitoring currently relies heavily on expensive and time-consuming radiological processes (CT/MRI/PET) or serial biopsies of tumours, which is often not practical.…”
Section: Tumour Clonality and Evolution Determines Tumour Aggressivenessmentioning
confidence: 99%